INTERLEUKIN LEVEL 10 AS A BIOMARKER IN IMPROVING TREATMENT OF PULMONARY TUBERCULOSIS BEFORE TREATMENT AND AFTER 2 MONTHS OF ANTI TUBERCULOSIS TREATMENT - Doddy Febryan, Parluhutan Siagian, & Ricke Loesnihari (International Journal of Research Science and Management, 2020)
Background Tuberculosis (TB) is an important community health problem in the world. Indonesia ranks third in the world after China and India. The cause of TB is Mycobacterium tuberculosis. The disease is the result of chronic interactions between intracellular microorganisms and the immune system response. Interleukin 10 (IL-10) is ananti-inflammatory cytokine. These cytokines are produced by macrophages and T cells during tuberculosis infection. The success of TB control is highly dependent on the diagnosis and appropriate treatment and evaluating its treatment. Many TB sufferers who are undergoing further anti tuberculosis treatment have difficulty sputum removal for acid-resistant bacillus smear examination, so that the therapeutic monitor is not optimal Methods Observational research with a cohort - prospective data collection method. Thirty subjects with positive smear pulmonary TB were taken blood samples, before treatment and after 2 months of anti tuberculosis treatment to assess changes in IL-10 levels Results From 30 patients with positive smear pulmonary TB disease, the IL value of 10 before receiving anti tuberculosis treatment was 17.9 ± 28.5 and after 2 months of treatment decreased to 13.6 ± 10.5,although this difference was not statistically significant (P <0.05). By using the Spearman correlation obtained a significant correlation between IL-10 levels before and after treatment (p <0.05) the correlation strength being moderate (r = 0.72) Conclusions From the results of the study concluded that there were nosignificant differences in IL-10 levels before and after two months of intensive phase treatment.